Assumptions and implementation of the policy of Polish government in the field of the development of shipbuilding industry in Poland in the context of the situation on the shipyard market in the world - Kamola-Cieślik, Małgorzata (Wydawnictwo Naukowe WNPiD UAM, 2019)
In 2015, Polish government announced the reconstruction of the shipbuilding industry, involving among others the companies established after the collapse of the shipyard in Szczecin in this process consisting in the construction of big modern ships. The aim of the article is to present the assumptions and realization of the policy of Polish government in the scope of the development of shipbuilding industry in Poland after the year 2015. Particular attention was paid to government’s decision aiming at the realization of shipbuilding industry development program in the context of the situation on global shipbuilding market. The attempts were undertaken to answer the following questions: What are the assumptions of the policy of Polish government in the context of the development of Polish shipbuilding industry after the year 2015?; What is the scope of realization of the assumptions of Polish governmental program addressed to the shipbuilding industry in the years 2016-2018? Is current policy of the government going to influence the establishment of a powerful center for the construction of ships within the premises of the former Szczecin shipyard? While aiming at finding the answers to research questions formulated in this way, the decision method was applied for the analysis of decisions made by the Council of Ministers concerning the implementation of the “Batory” program. The institutional and legal method was used while presenting the establishment of institutional conditions of the environment of maritime economy. In turn, thanks to the comparative method it was presented to what extent the assumptions of the governmental program concerning the development of the shipbuilding industry were realized in the years 2016-2018. Basing on the conducted research it should be stated that the establishing of a powerful center for the construction of big ships within the premises of the former Szczecin shipyard may constitute a difficult task due to insufficient experience of MSR Gryfia in the construction of such specialized vessels as passenger and freight ferries. Another issue consists in the shortage of qualified staff, damaged infrastructure of former Szczecin shipyard which requires additional funds, not specified source of funding of the “Batory” program as well as the crisis in global shipbuilding industry from the year 2016, strictly connected with reduced number of orders.

W 2015 r. rząd polski zapowiedział odbudowę przemysłu stoczniowego, angażując między innymi firmy powstałe po upadku stoczni w Szczecinie w budowę nowoczesnych dużych statków. Celem artykułu jest przestawienie założeń i realizacji polityki rządu polskiego w zakresie rozwoju przemysłu stoczniowego w Polsce po 2015 roku. Szczególną uwagę zwrócono na decyzje rządu w celu realizacji programu rozwoju przemysłu stoczniowego w kontekście sytuacji rynku stoczniowego na świecie. Starano się odpowiedzieć na pytania: Jakie są założenia polityki rządu polskiego w zakresie rozwoju przemysłu stoczniowego w Polsce po 2015 r., biorąc pod uwagę sytuację rynku stoczniowego na świecie?; W jakim zakresie założenia programu rządu polskiego wobec przemysłu stoczniowego zostały zrealizowane w latach 2016-2018? Czy obecna polityka rządu wpłynie na powstanie silnego ośrodka budowy statków na terenie byłej stoczni szczecińskiej? Dążąc do uzyskania odpowiedzi na postawione pytania badawcze, wykorzystano metodę decyzyjną, analizując decyzje Rady Ministrów dotyczące wdrażania programu „Batory”. Metodę instytucjonalno-prawną zastosowano ukazując powstanie instytucjonalnych warunków do rozwoju gospodarki morskiej. Z kolei dzięki metodzie komparatystycznej przedstawiono w jakim zakresie założenia rządowego programu dotyczące rozwoju przemysłu stoczniowego zostały zrealizowane w latach 2016-2018. Na podstawie przeprowadzonych badań należy stwierdzić, że powstanie silnego ośrodka budowy dużych statków na terenach byłej stoczni szczecińskiej może okazać się trudne z braku doświadczeń MSR Gryfia w budowie tak specjalistycznych statków, jakimi są promy pasażersko-towarowe. Innym problemem jest brak wykwalifikowanej kadry, zdegradowana i wymagająca doinwestowania infrastruktura po byłej stoczni w Szczecinie, brak wskazania źródła finansowania programu „Batory” oraz trwający od 2016 r. kryzys branży stoczniowej na świecie związany z redukcją zamówień.
Założenia i realizacja polityki rządu polskiego w zakresie rozwoju przemysłu stoczniowego w Polsce w kontekście sytuacji na rynku stoczniowym w świecie
Keywords: policy of the government; political decisions; maritime economy; shipbuilding industry; European Union; polityka rządu; decyzje polityczne; gospodarka morska; przemysł stoczniowy; Unia Europejska